The Right to Access to a Lawyer at Police Stations: Making the European Union Directive Work in Practice. Issue 4 (December 2014) - Cape, Ed; Hodgson, Jacqueline
Recent EU Directives provide for a range of procedural protections for suspects and accused persons, going beyond the more broadly articulated standards set out in the European Convention of Human Rights. These reforms are to be welcomed, but their implementation poses a range of challenges for Member States. Drawing on recent empirical research, this article focuses on one measure, the right to legal assistance during police custody. It discusses the range of complex and often inter-related factors that operate to help or to hinder the process of ensuring that the right is 'practical and effective' and not merely 'theoretical and illusory'. Member States do not share a common procedural tradition and alongside ensuring sufficient financial and human resources, effective implementation will require shifts in the legal and occupational cultures of police, prosecutors and the criminal bar.